Engaging Millennial Students through Community-Engaged Experiential Learning - Andrade , Maureen Snow; Westover , Jonathan H. (Experiential Learning and Teaching in Higher Education, 2022)
Millennial students and workers are high-achieving, have a strong desire for ongoing personal and professional development, and tend to be invested in making a sustainable impact on society and in the communities in which they live and work. One avenue to engage these students is community-engaged experiential learning (or service learning). While service learning is not new, this “civically-engaged” pedagogy has increased in popularity and usage. It provides meaningful community-service opportunities that simultaneously teach civic responsibility and encourage life-long civic engagement, while also providing significant real-life, hands-on learning of important skills and vital social understanding. This quantitative study examines the connections between students’ motivations for enrolling in service-learning courses and their perceived likelihood for course and program completion. It also connects student motivations for enrolling in service-learning courses to the literature on millennial students and preparing students for the future workforce. Findings not only identify gains in service-learning motivations overall, but also specific volunteerism motivations that contribute to students’ expressions of intent for course and program completion. The findings also demonstrate that study participants exhibited typical characteristics associated with the millennial generation and that these are strengthened through service-learning participation